Penerimaan Khalayak pada Konten Youtube Gamal: Episode Akar Permasalahan di Dunia - Muhammad Fa’isal; Rakhmad S. Ramadhani; Masnia Ningsih (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
Neo-feudalism Analisis Resepsi, Fariz Egia Gamal, Akar Permasalahan Di Dunia, Neo Feodalisme describes the resurgence of social and economic patterns resembling medieval feudalism in a modern context. This phenomenon is characterized by increasing social and economic inequality and the concentration of wealth and influence among a few individuals or groups, reflects a distribution structure similar to that implemented in the feudal system of the past. This study aims to analyze the audience reception of Gamal's YouTube content in the episode "Root Problems in the World." The research utilizes Stuart Hall's reception analysis methodology, with data collected through observation and documentation techniques. The analysis is based on three categories (Dominant Hegemonic Position, Negotiated Position, and Oppositional Position) of audience comments on Gamal's YouTube content in the episode "Root Problems in the World." The results show that out of 300 comments interpreting Gamal’s YouTube content in the episode "Root Problems in the World," 265 comments fall into the dominant hegemonic position, 30 comments fall into the negotiated position, and 5 comments fall into the oppositional position.